Estimation of genetic parameters for udder quality in Hereford cattle - Bradford, Heather Lynn (Kansas State University, 2013)
Udder quality is an important trait for beef producers because udders impact cow longevity and calf performance. The objective of this study was to estimate the genetic parameters for udder quality in Hereford cattle. The Beef Improvement Federation recommends collecting subjective scores on udder suspension and teat size. Prior to these guidelines, the American Hereford Association (AHA) recorded an overall score, which combines all udder characteristics into a single score. In all cases, scores ranged from 1 to 9 with a score of 9 considered ideal. Records on 78,556 animals and a 3-generation pedigree with 196,540 animals were obtained from the AHA, Kansas City, MO. These records contained repeated observations for overall score (n=126,753), suspension (n=61,758), and teat size (n=61,765). Data were modeled using a multiple trait animal mixed model with random effects of additive genetic and permanent environment and with fixed effects of age and contemporary group (herd-year-season). Variances were estimated with ASREML 3.0. Heritability estimates (standard errors) of overall score, suspension, and teat size were 0.32 (0.01), 0.31 (0.01), and 0.28 (0.01), respectively. These results showed udder quality was moderately heritable, agreeing with previous research. The phenotypic correlation (standard error) between teat size and suspension was 0.64 (0.003). Of the records for suspension and teat size, 57% had the same score for both traits. The genetic correlations (standard errors) between teat size and suspension, overall score and teat size, and overall score and suspension were 0.83 (0.01), 0.72 (0.02), and 0.70 (0.02), respectively. The genetic correlations between traits were extremely strong. In addition, producer education is important to ensure the scoring systems are used correctly.
Keywords: Beef cattle; Genetic parameters; Udder score; Animal Sciences (0475)